2018
DOI: 10.1002/hbm.24224
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise modulates anticipatory reward processing via the μ‐opioid receptor system

Abstract: Physical exercise modulates food reward and helps control body weight. The endogenous µ-opioid receptor (MOR) system is involved in rewarding aspects of both food and physical exercise, yet interaction between endogenous opioid release following exercise and anticipatory food reward remains unresolved. Here we tested whether exercise-induced opioid release correlates with increased anticipatory reward processing in humans. We scanned 24 healthy lean men after rest and after a 1 h session of aerobic exercise wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Given that there are underlying differences in neural reward processing in individuals with obesity relative to normal-weight controls [ 41 ] and between physically inactive versus highly trained athletes [ 42 ], it is plausible that exercise engagement may mitigate some maladaptive behavioral reward responsivity. These findings are consistent with literature from both human and animal models demonstrating that engagement in exercise alters neurophysiological responses to rewards (e.g., opioid receptor binding, dopaminergic or glutamatergic signaling, respectively), thereby improving reward sensitivity [ 43 , 44 ]. Importantly, both the DIET + MODEX and DIET groups showed declines in IGT reward sensitivity, although the DIET group declined to a greater extent than the exercise group.…”
Section: Discussionsupporting
confidence: 89%
“…Given that there are underlying differences in neural reward processing in individuals with obesity relative to normal-weight controls [ 41 ] and between physically inactive versus highly trained athletes [ 42 ], it is plausible that exercise engagement may mitigate some maladaptive behavioral reward responsivity. These findings are consistent with literature from both human and animal models demonstrating that engagement in exercise alters neurophysiological responses to rewards (e.g., opioid receptor binding, dopaminergic or glutamatergic signaling, respectively), thereby improving reward sensitivity [ 43 , 44 ]. Importantly, both the DIET + MODEX and DIET groups showed declines in IGT reward sensitivity, although the DIET group declined to a greater extent than the exercise group.…”
Section: Discussionsupporting
confidence: 89%
“…However, liking and implicit wanting were not measured directly in these studies (i.e., behavioral measures) nor was food intake. Lastly, Saanikoji et al found no effect of an acute moderate-intensity aerobic exercise on brain food reward in lean men [52]. However, they showed that individuals who increased the most in endogenous opioid release had the highest brain reward response after the exercise compared with the control.…”
Section: Acute Exercise Studiesmentioning
confidence: 98%
“…Furthermore, changes in MOR binding after aerobic exercise are associated with changes in brain responses to foods versus nonfoods, and to palatable versus nonpalatable foods as measured using fMRI. 105,106…”
Section: Pet/mri Of Endogenous Neurotransmitter Release By Pharmacolomentioning
confidence: 99%